Front Matter - Gunadnya, Ida Bagus Putu (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2020)
Front matter contains cover of the journal, brief description of the journal, Editorial Board, Reviewers that had made contribution, and table of content. Front matter is usually not more than six pages length.